Tick saliva protein fraction inhibits breast cancer by decreasing cell viability and promoting apoptosis in vitro - Ana Carolina Prado Sousa; Mario Durán-Prado; Margarita Villar; Almudena González-García; Matias Pablo Juan Szabó; José de la Fuente (PLoS ONE, 2025)
Tick saliva contains protein and non-protein bioactive molecules with potential therapeutic applications, including anticancer properties. In this study, the effects of protein and non-protein fractions of saliva from different tick species (Amblyomma spp. and Rhipicephalus sanguineus) at various concentrations (0.1–10 µg/mL) were tested on the viability, apoptosis, and necrosis of epithelial MDA-MB-231 breast cancer cells and spontaneously immortalized HaCaT cell control. Chemical composition of tick saliva from A. parvum and A. sculptum was characterized by proteomics analysis. Cell viability was assessed using a calcein-based fluorescence method. Hoechst staining quantified the total number of cells per well, while apoptosis and necrosis were evaluated using Hoescht and propidium iodide assays, respectively. On MDA-MB-231 cancer cells, the protein fraction from A. parvum and R. sanguineus significantly reduced cell viability at the highest concentration (10 µg/mL), whereas A. sculptum and non-protein fractions showed no significant effect. Hoechst staining revealed a significant reduction in cell attachment at 10 µg/mL for A. parvum and R. sanguineus. A modest apoptosis (3–8%) was induced by the protein fractions at concentrations as low as 0.1 µg/mL for R. sanguineus and 10 µg/mL for the non-protein fraction of A. sculptum. Necrosis was not observed, except for a slight increase (1%) with the protein fraction of R. sanguineus at 10 µg/mL. No effect of A. americanum tick saliva protein and non-protein fractions was observed in HaCaT control cells. The results of highly represented proteins identified in Amblyomma spp. correlated with effect of tick saliva protein fraction on cancer cells, highlighting the potential anticancer properties of tick saliva protein fraction, which can induce apoptosis and inhibit cell attachment in breast cancer cells. These findings provide a basis for future studies of tick saliva components as novel therapeutic agents and identifying active biomolecules and mechanisms of action.